1994
DOI: 10.1152/ajpendo.1994.266.5.e750
|View full text |Cite
|
Sign up to set email alerts
|

Splanchnic and systemic absorption of intraperitoneal insulin using a new double-tracer method

Abstract: The absorption of a bolus of intraperitoneal insulin into the splanchnic and peripheral circulations was separately assessed in dogs using an infusion of two insulin tracers (A1-[3H]insulin and B1-[3H]insulin). One tracer was infused into the superior mesenteric artery and the second into the jugular vein. Serial samples were taken before and after an injection of insulin (1 U/kg ip). Sampling was from the portal vein and the inferior vena cava. By using the principle of equivalent entry of tracer and unlabele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…This decline, therefore, contributes approximately 50% to the overall development of hyperinsulinemia, the remainder of the increase being related to β-cell hypersecretion of insulin. Using a double-label method to measure MCRI and hepatic extraction of exogenous insulin in conscious dogs, Pye et al also reported that as portal insulin levels were increased from basal level to 3,738 pM, hepatic insulin uptake decreased from 61% to 29%, while the MCRI declined 3 fold [30]. These data are in accord with the reports that a saturation of hepatic insulin extraction occurs at elevated insulin concentrations approaching 1,800 pM in anesthetized dogs [31], 1,804 - 1,955 pM in dysmetabolic rhesus monkeys [6], and 1,680 pM in men during exogenous insulin infusion [32].…”
Section: Discussionmentioning
confidence: 99%
“…This decline, therefore, contributes approximately 50% to the overall development of hyperinsulinemia, the remainder of the increase being related to β-cell hypersecretion of insulin. Using a double-label method to measure MCRI and hepatic extraction of exogenous insulin in conscious dogs, Pye et al also reported that as portal insulin levels were increased from basal level to 3,738 pM, hepatic insulin uptake decreased from 61% to 29%, while the MCRI declined 3 fold [30]. These data are in accord with the reports that a saturation of hepatic insulin extraction occurs at elevated insulin concentrations approaching 1,800 pM in anesthetized dogs [31], 1,804 - 1,955 pM in dysmetabolic rhesus monkeys [6], and 1,680 pM in men during exogenous insulin infusion [32].…”
Section: Discussionmentioning
confidence: 99%
“…In either case, hepatic glucose production was not suppressed appropriately, most likely because insulin delivery was poorly coupled to feeding activity. Even so, we anticipated that hepatic metabolic fluxes of STZ rats would respond better to I-IP vs. I-SC, since I-IP better recreates the physiological portal-peripheral insulin gradient (47). Postprandial glycogen was lower in I-SC than in controls, whereas I-IP resulted in its normalization to control levels.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of insulin into the free peritoneal cavity with absorption into both the portal and peripheral systems has been done in humans [2][3][4]. This approach using a subcutaneous "button" reservoir for injection and release of insulin has succeeded in establishing glucose control and stabilizing diminished renal function in a group of patients, but fibrosis of catheter tip and steatotic changes at liver surface [5] due to altered triglyceride metabolism have limited use of intraperitoneal insulin placement.…”
Section: Discussionmentioning
confidence: 99%